Changeover method for biosafety cabinets using ozone gas. - Mitsuru Mizuno; Daisuke Suda; Chima Matsumura; Ichiro Sekiya (PLoS ONE)
This study evaluated the effectiveness of a biosafety cabinet equipped with an ozone generator, particularly during the transition periods between the production of cell products. As living cell products cannot undergo sterilization, maintaining an aseptic manufacturing environment is paramount. Raw materials, often derived from human tissues, are frequently contaminated with various resident bacteria, necessitating environmental resets after each process. The utility of this device against bacteria, including endotoxins, endospores, and fungi endemic to human tissues, could facilitate safe and reproducible production changeovers through a simplified, one-button operation. This study focused on bacteria resistant to conventional cleaning protocols, specifically targeting endospore-forming bacteria with robust resistance to disinfectants, spore-forming fungi, and included analyses of endotoxins. The effects of ozone exposure on Pseudomonas aeruginosa (an endotoxin-producing bacterium), Bacillus subtilis (an endospore-forming bacterium), and Aspergillus brasiliensis (a spore-forming fungus) were assessed. In the dedicated biosafety cabinet equipped with an ozone generator, the treatment group exposed to ozone showed a significant reduction in both colony-forming units and endotoxin levels in Pseudomonas aeruginosa at 1.0 × 104 colony-forming units (CFUs) compared to the control group. Moreover, the ozone treatment markedly decreased the colony formation of Bacillus subtilis endospores and Aspergillus brasiliensis spores. Given its effectiveness against endospores and endotoxins-among the most challenging bacterial derivatives to eliminate-the device demonstrates potential for enhanced bacterial control in Grade A biosafety cabinets within cell product manufacturing facilities. The system may substantially reduce operator stress by ensuring product safety through straightforward operational procedures and high reproducibility, although further validation is required.